2018
DOI: 10.1097/jom.0000000000001437
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Woodsmoke Exposure During Exercise and Blood Oxidative Stress

Abstract: Blood oxidative stress occurred largely independent of PM2.5 concentrations. Future studies should employ longer duration smoke and exercise combined with physiologic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Abbreviations are denoted in the list of abbreviations in main text Ghio et al [ 16 ] Sehlstedt et al [ 20 ] Ferguson et al [ 22 ] Peters et al [ 24 ] Barregard et al [ 25 , 26 ] Danielsen et al [ 27 ] Murgia et al [ 28 ] Stockfelt et al [ 29 , 30 ] Forchhammer et al [ 32 ] Muala et al [ 35 ] Emissions Major PM class OC OC/Soot OC/Soot OC/Soot OC/Soot Soot/Ash Soot/Ash Exposure time 2 h 3 h 1.5 h 4 h 3 h 3 h 3 h Exercise (y/n) yes yes yes yes no no yes PM 2.5 conc. (μg/m 3 ) 485 224 low – 253.9 high – 506.2 243–279 SUP – 221 BOP – 148 low – 220.5 high – 352.38 314 Biomarkers Serum UA a ↓ at 1.5 h (combined) [ 24 ] Serum TEAC a ↑ at 1.5 h, 2.5 h (combined) [ 24 ] Serum oxidative damage markers 8-iso ↑ at 1.5 h (high and low) [ 24 ] LOOH ↓ at 2.5 h...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Abbreviations are denoted in the list of abbreviations in main text Ghio et al [ 16 ] Sehlstedt et al [ 20 ] Ferguson et al [ 22 ] Peters et al [ 24 ] Barregard et al [ 25 , 26 ] Danielsen et al [ 27 ] Murgia et al [ 28 ] Stockfelt et al [ 29 , 30 ] Forchhammer et al [ 32 ] Muala et al [ 35 ] Emissions Major PM class OC OC/Soot OC/Soot OC/Soot OC/Soot Soot/Ash Soot/Ash Exposure time 2 h 3 h 1.5 h 4 h 3 h 3 h 3 h Exercise (y/n) yes yes yes yes no no yes PM 2.5 conc. (μg/m 3 ) 485 224 low – 253.9 high – 506.2 243–279 SUP – 221 BOP – 148 low – 220.5 high – 352.38 314 Biomarkers Serum UA a ↓ at 1.5 h (combined) [ 24 ] Serum TEAC a ↑ at 1.5 h, 2.5 h (combined) [ 24 ] Serum oxidative damage markers 8-iso ↑ at 1.5 h (high and low) [ 24 ] LOOH ↓ at 2.5 h...…”
Section: Resultsmentioning
confidence: 99%
“…Although a slight decrease in forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC), and the ratio of these values (FEV 1 /FVC) was observed, none of these results reached significance. With regard to oxidative stress markers in the same study, Peters et al [24] reported that uric acid (UA) values decrease immediately post-exposure and plasma Trolox equivalent antioxidant capacity (TEAC) levels were increased both immediately after and 1 h after the exposure. A biomarker for plasma oxidative stress, lipid hydroperoxides (LOOHs), was decreased 1 h post-exposure, while 8-iso, 3-nitrotyrosine (3-NT) and plasma MPO increased immediately post WS-exposure.…”
Section: Study-specific Methods and Outcomesmentioning
confidence: 91%
See 3 more Smart Citations